Conflict Between The Muslims And Sikhs In Partition Movie Directed By Vic Sarin (2007): A Sociological Approach - Yulianti, Rani, Drs. M. Thoyibi, M.S, Nur Hidayat, S.Pd (2013)
This study is about conflict between Muslims and Sikhs in Partition movie. The major problem in this research paper is to describe how conflict between Muslim and Sikh in Partition movie. The objectives of the study are to analyze Sarin's Partition movie based on the structural elements of the movie. To describe conflict between Muslim and Sikh in Partition movie based on sociological approach. The object of study is Partition movie by Vic Sarin. It used sociological approach. The writer uses qualitative methodology of research and sociological approach in analyzing this study. The Primary data source of this research is the movie Partition movie that movie by Vic Sarin and synopsis of Partition movie. The secondary data sources are the author's biography, essay, comment, homepage, and website about the movie and other relevant sources. The result of the study shows the following conclusions. First, based on structural analysis the director delivers a message that different religions may cause horizontal conflicts. Second, based on the sociological analysis the movie reflects the social reality of the Indian society at the end of the twentieth century and early twenty-first century. The dominant aspect of the social reality is the diverse ethnic and religious groups. The director of the movie also criticizes that people should recognize others in order to build peace.